Analisis Toksisitas Akut Kombinasi Captopril dengan Rebusan Daun Sirsak pada Tikus Galur Wistar - Rina Saputri; Mustaqimah Mustaqimah; Ali Rakhman Hakim (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Hypertension is a degenerative disease that requires lifelong therapy. Along with the development of time, nowadays people are more interested in consuming traditional medicine, especially by using plants. In addition to consuming soursop leaf decoction, people also continue to use conventional medicine to help control hypertension. The combination of conventional medicine and traditional medicine can cause unwanted reactions if not used in the right dosage, one of which is the risk of acute toxicity. Until now there is no published data showing the acute toxicity analysis of the combination of captopril with soursop leaf decoction. The purpose of the study was to determine the maximum dose of the combination of captopril and soursop leaf decoction that could be used. The method used in this study is an advanced experimental study with a random block design using 30 test animals divided into 10 groups. The results of the acute toxicity test conducted did not show any death of the test animals within 24 hours and up to 7 days of observation in all experimental groups. The results of the physical observation test for 7 days showed that all rats were in normal condition in all experimental groups. The conclusion of this study is that the combination of captopril up to a dose of 150 mg/day (dose in humans before conversion to test animals) + soursop leaf decoction with an effective dose of 300 ml (dose in humans before conversion to test animals) did not show any death and symptoms toxicity in test animals.